Find (i) β« ln π₯ ππ₯, (ii) β« π βπ₯ cos 2π₯ ππ₯. Hint: Let πΌ = β« π π₯ cos 2π₯ ππ₯ and use parts twice, (iii) sinβ1 π₯ ππ₯.
Solution:
(i)
"I=\\int\\ln x\\ dx\n\\\\=\\int1\\times\\ln x\\ dx"
Using integration by parts,
"I=\\ln x\\int1\\ dx-\\int(\\dfrac d{dx}\\ln x\\int1dx)dx\n\\\\=\\ln x \\times x-\\int(\\dfrac 1{x}\\times x)dx\n\\\\=x\\ln x -x+C"
(ii)
"I=\\int e^{-x}\\cos 2x\\ dx" ...(A)
Using integration by parts,
"I=\\cos 2x\\int e^{-x} dx-\\int(\\dfrac d{dx}\\cos 2x \\int e^{-x}dx)dx\n\\\\=\\cos 2x \\times- e^{-x} -\\int(-2\\sin 2x \\times-e^{-x})dx\n\\\\=- e^{-x}\\cos 2x -2\\int(\\sin 2x \\times e^{-x})dx"
Again, using integration by parts,
"I=- e^{-x}\\cos 2x -2[\\sin 2x \\int e^{-x}dx-\\int(\\dfrac d{dx}\\sin 2x \\times \\int e^{-x}dx)dx]"
"=- e^{-x}\\cos 2x -2[-e^{-x}\\sin 2x -\\int(2\\cos 2x \\times - e^{-x})dx]\n\\\\=- e^{-x}\\cos 2x +2e^{-x}\\sin 2x -4\\int(\\cos 2x \\times e^{-x})dx"
"I=- e^{-x}\\cos 2x +2e^{-x}\\sin 2x -4I+C" [Using (A)]
"5I=- e^{-x}\\cos 2x +2e^{-x}\\sin 2x +C\n\\\\\\Rightarrow I=\\dfrac15(2e^{-x}\\sin 2x- e^{-x}\\cos 2x +C)"
(iii)
"I=\\int \\sin^{-1}x \\ dx\n\\\\=\\int 1\\times \\sin^{-1}x \\ dx"
Using integration by parts,
"I=\\sin^{-1}x\\times\\int 1 \\ dx-\\int(\\dfrac d{dx}\\sin^{-1}x\\int1 dx)dx\n\\\\=\\sin^{-1}x\\times x-\\int(\\dfrac 1{\\sqrt{1-x^2}}\\times x)dx"
"=x\\sin^{-1}x-\\dfrac12\\int\\dfrac {2x}{\\sqrt{1-x^2}}dx\n\\\\=x\\sin^{-1}x-\\dfrac12I_1+C"
Now, "I_1=\\int\\dfrac {2x}{\\sqrt{1-x^2}}dx"
Put "1-x^2=t"
"\\Rightarrow 2xdx=-dt"
So, we get,
"I_1=-\\int\\dfrac {1}{\\sqrt{t}}dt=-\\int t^{-1\/2} dt=-\\dfrac{t^{1\/2}}{1\/2}=-2\\sqrt t=-2\\sqrt{1-x^2}"
Thus, "I=x\\sin^{-1}x-\\dfrac12(-2\\sqrt{1-x^2})+C"
"\\Rightarrow I=x\\sin^{-1}x+\\sqrt{1-x^2}+C"
Comments
Leave a comment